AN ANALYTICAL REVIEW OF HEALTH INSURANCE PENETRATION AND ITS EFFECT ON HEALTHCARE ACCESSIBILITY IN NASHIK DISTRICT - Aher, Varsha Ganeshchandra; Gite, Urmila Yogesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The current research focuses on the extent of health insurance in health care sector in Nashik District and its repercussions on health care accessibility. It is a mixed-methods research in which descriptive survey data of 300 residents are collected and complemented with interviews of healthcare professionals and insurance specialists. The data show that is still pertinent that Health Insurance in Nashik District at comparatively low level and only 35% of people have Health Insurance in Nashik District. This has a very limiting effect on people’s ability to get health care because residents who are uninsured end up paying more out of their own pocket and this slows them down in seeking medical care. Also, findings suggest that patients with health insurance have shorter waiting times and better overall satisfaction with, and improved health status compared to those without insurance. The papers warns the public of the need for policies to expand on health insurance since it is a key factor to improving on access to health care. This research supports the broader health system discussions in Nashik District by Asian Public Nations, specifically focusing on the concerns of penetration and accessibility of Health Insurance, and makes a positive call for Health Insurance policies that make health care more accessible to all people.